PATOGENITAS ISOLAT BAKTERI ASAM LAKTAT DARI USUS IKAN REPANG (Puntioplites waandersi) TERHADAP IKAN NILA (Oreochromis niloticus) - Agustina Agustina; Puput Andriani; Gina Saptiani (Jurnal Akuakultur Rawa Indonesia, 2023)
This study aims to determine the pathogenicity of lactic acid bacteria from repang fish on clinical symptoms, anatomical pathology, hematological and survival rate of tilapia (Oreochromis niloticus). This reseach used a completely randomized design with 5 treatments and 3 replications, namely PBS 0.1 mL/fish, A. hydrophilla 106 CFU/ml as much as 0.1 mL/fish, Enterococcus sp. 106 CFU/ml as much as 0.1 mL/fish, Lactobacillus sp. 106 CFU/ml as much as 0.1 mL/fish and Lactococcus sp. 106 CFU/ml as much as 0.1 mL/fish. Treatment of the bacteria to fish were used intra muscular injection. Clinical symptoms, anatomical pathology and hematological were analyzed descriptively, while survival was analyzed statistically using ANOVA. Tilapia with an average weight of 30 g/fish were reared for 7 days in an aquarium measuring 50×40×30 cm3 with a volume of 40 L of water, at a density of 10 fish/aquarium. Fish are fed 3 times a day. Administration of lactic acid bacteria Lactobacillus sp. showed the highest survival rate compared to the treatment with other isolates. Hematological were in the normal range in all treatments except for the treatment with A. hydrophila bacteria. The three lactic acid bacteria from the intestines of repang fish are safe for tilapia and can be used in further probiotic tests.  Keywords: Lactid acid bacteria, pathogenicity, A. hydrophila, hematology